2023
DOI: 10.7150/ijms.80358
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Fingerprint Associated with Familial Idiopathic Pulmonary Fibrosis: A Review

Abstract: Idiopathic pulmonary fibrosis (IPF) is a severe interstitial lung disease; although the recent introduction of two anti-fibrosis drugs, pirfenidone and Nidanib, have resulted in a significant reduction in lung function decline, IPF is still not curable. Approximately 2-20% of patients with IPF have a family history of the disease, which is considered the strongest risk factor for idiopathic interstitial pneumonia. However, the genetic predispositions of familial IPF (f-IPF), a particular type of IPF, remain la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 189 publications
0
2
0
Order By: Relevance
“…When the UPR cannot rectify protein misfolding, it triggers the terminal UPR, leading to cell death [106]. Several researchers have reported increased markers of UPR activation in alveolar epithelial cells (AEC) type II cells in IPF [107].…”
Section: Geneticmentioning
confidence: 99%
See 1 more Smart Citation
“…When the UPR cannot rectify protein misfolding, it triggers the terminal UPR, leading to cell death [106]. Several researchers have reported increased markers of UPR activation in alveolar epithelial cells (AEC) type II cells in IPF [107].…”
Section: Geneticmentioning
confidence: 99%
“…It has been shown that familial pulmonary fibrosis [110] is associated with mutations in telomerase genes (Table 2, Ref. [107,[111][112][113]).…”
Section: Geneticmentioning
confidence: 99%